International Society on Thrombosis and Haemostasis core curriculum project: core competencies in clinical thrombosis and hemostasis. (6th January 2016) - McLintock, C.; Pabinger, I.; Bauer, K. A.; Laffan, M.; Angchaisuksiri, P.; Rezende, S. M.; Middeldorp, S.; Ross, M.
Abstract : Essentials The priority of ISTH was to establish a global core curriculum in thrombosis and hemostasis. International survey to determine competencies required for clinical specialists was carried out in the field. Competency framework provides a reference point for mapping and developing regional curricula. Core curriculum informs and links to a variety of ISTH educational materials. Summary: Background: The International Society on Thrombosis and Haemostasis (ISTH) identified the need for an international core curriculum on thrombosis and hemostasis for its society members and the larger thrombosis and hemostasis community. Aims: The current research sought consensus on the core competencies required by medical doctors who are ready to practise as independent clinical specialists in thrombosis and hemostasis with the aim of developing a core clinical curriculum for specialists in the field. Method: A draft list of competencies was developed by the Working Group and formed the basis of an online survey. ISTH members and the larger thrombosis and hemostasis community were asked to rate the importance of each competency, on a Likert scale, for clinical specialists in thrombosis and hemostasis. Results: There were a total of 644 responses to the online survey with broad geographical representation. There was general agreement on what level of competency would be required for clinical specialists in thrombosis and hemostasis at the specified level of training. Conclusions: Using the survey to gain consensus on the level of competency required by clinical specialists in the field of thrombosis and hemostasis enabled the development of a core clinical curriculum that has been endorsed by the ISTH Council. The curriculum will offer a framework and international reference that will be used by the society, by national and regional organizations, and for further research.